Worsened outcome in patients with pancreatic ductal carcinoma on long-term diabetes: association with E-cadherin1 (CDH1) promoter methylation. Issue 1 (December 2017) - Saito, Takeshi; Mizukami, Hiroki; Umetsu, Satoko; Uchida, Chiaki; Inaba, Wataru; Abe, Makoto; Takahashi, Kazuhisa; Kudo, Kazuhiro; Itabashi, Chieko; Yagihashi, Soroku; Hakamada, Kenichi
Abstract Prevalence of pancreatic ductal carcinoma (PDC) is nearly twice in patients with diabetes mellitus, but the reason for this close association remains obscure. Recently promoter methylation of E-cadherin1 (CDH1) and CDKN2A genes, encoding E-cadherin and P16 respectively, are invoked in development of PDC. It is still unclear whether diabetes affects such epigenetic changes and malignant behavior in PDC. In this study, we studied whether diabetes influences the clinico-pathological profile and methylation status of CDH1 and CDKN2A genes in patients with PDC. PDC subjects were divided into 3 groups; 59 cases without diabetes (non-DM), 17 cases with short-term diabetes (short-DM)(diabetes duration 3 yrs>) and 33 cases with long-term diabetes (long-DM)(≧3 yrs). Compared to non-DM or short-DM, long-DM was associated with a higher histological grade of malignancy and a higher tumor stage. Promoter methylation of both CDH1 and CDKN2A was encountered more frequently in PDC patients with long-DM than non-DM or short DM. Cases with CDH1 promoter methylation showed reduced E-cadherin expression and worsened survival. We consider that the presence of long-DM has a negative impact on the prognosis of PDC patients which may be relevant to a high frequency of promoter methylation of CDH1.